Genetic typing of bovine viral diarrhea virus isolates from Costa Rica (Ciencias Veterinarias, 2012)
Sixteen bovine viral diarrhea virus (BVDV) isolates collected in Costa Rica between 1987 and 2006 from dairycattle were analyzed by RT-PCR and determined to belong to BVDV species 1. Furthermore, eleven of theseisolates were genotyped using the nucleotide sequences of the Npro region of the viral genome. Phylogeneticanalysis indicated that all samples examined clustered within the BVDV-1b subtype.